1994
DOI: 10.1089/thy.1994.4.65
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cell Lesions of the Thyroid: Report of a Case of Solitary Plasmacytoma and a Review of the Literature

Abstract: We report a case of a solitary plasmacytoma arising from a thyroid with longstanding Hashimoto's disease, and diagnosed by fine-needle aspiration cytology. Serum protein electrophoresis revealed an M-spike in the gamma-globulin region due to monoclonal IgG-lambda immunoglobulin. The thyroid tumor was treated with near-total thyroidectomy and irradiation, and the patient was well 6 years after surgery without evidence of multiple myeloma. The serum M-spike disappeared after the tumor resection and radiation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…More than 60 cases were documented in the English literature. 21 The plasmacytomas were slightly more common in women (male/female ratio, 1:1.3). The mean age at initial examination was 62 years (range, 32 to 87 years).…”
Section: Discussionmentioning
confidence: 99%
“…More than 60 cases were documented in the English literature. 21 The plasmacytomas were slightly more common in women (male/female ratio, 1:1.3). The mean age at initial examination was 62 years (range, 32 to 87 years).…”
Section: Discussionmentioning
confidence: 99%
“…FNAC of thyroid primary malignant lymphoma is useful as a preoperative qualitative diagnostic procedure, and previous studies have attempted to improve the diagnostic accuracy of FNAC [6,7,8,9,10,11,12,13,14,15,16,17,18,19,22,23,24,25,26,27,28,29,30,31]. However, some of those studies [8,9,10,11,12,17,22,23,24,25,26,27,29,30] did not include any cases of MALT lymphoma, while those that did [7,13,14,15,16,17,18,19,28,31] only examined a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of those studies [8,9,10,11,12,17,22,23,24,25,26,27,29,30] did not include any cases of MALT lymphoma, while those that did [7,13,14,15,16,17,18,19,28,31] only examined a few cases. For this reason, we considered the present conditions for cellular analysis based on the concept of MALT lymphoma to be insufficiently accurate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases may complicate Hashimoto's thyroiditis. 20 EMP is composed of a monomorphous population of plasma cells instead of a mixed population of lymphocytes, plasma cells, and lymphoplasmacytoid cells seen in MALT lymphoma. It has been suggested that cases previously reported as EMP of the thyroid represent MALT lymphoma with extreme plasma-cell differentiation 10,21 because the clinical behavior appears similar.…”
Section: Discussionmentioning
confidence: 99%